Man-Bites-Dog Business Cycles - Nimark, Kristoffer P. (American Economic Review, 2014)
The newsworthiness of an event is partly determined by how unusual it is and this paper investigates the business cycle implications of this fact. Signals that are more likely to be observed after unusual events may increase both uncertainty and disagreement among agents. In a simple business cycle model, such signals can explain why we observe (i) occasional large changes in macroeconomic aggregate variables without a correspondingly large change in underlying fundamentals, (ii) persistent periods of high macroeconomic volatility and, (iii) a positive correlation between absolute changes in macrovariables and the cross-sectional dispersion of survey expectations. (JEL D81, D82, D84, E23, E31, E32)